Pengaruh pemberian campuran mikoriza-Trichoderma sp. Dan pengurangan dosis pupuk NPK terhadap penyimpanan umbi bawang merah - Faizal Surya Wibawa; Eny Rokhminarsi; Ni Wayan Anik Leana (Jurnal AGRO, 2023)
Shallot storage is very important for the availability throughout the year. The use of mixed bio-fertilizers Mycorrhiza and Trichoderma sp. combined with reduced doses of NPK fertilizer is expected to increase the shelf-life of shallot bulbs. The study used a two-factorial Completely Randomized Block Design with the first factor was mycorrhizae-Trichodermasp. biofertilizer, and second factor was reduced NPK fertilizer applied during the cultivation stage. Storage research was carried out for 60 days to determine the dosage of mycorrhiza-Trichoderma sp., the dose of NPK fertilizer, and the combination of doses of mycorrhiza-Trichoderma sp. and the best NPK fertilizer for shallot storage. The results showed that the application of mycorrhiza-Trichoderma sp. affected the volume, shelf-life, and color of shallot bulbs. Reducing the doses of NPK fertilizer affected the color of the tubers. The interaction between the application of mycorrhiza-Trichoderma sp. and reduced doses of NPK fertilizer affected weight loss, diameter, aroma, and rotten tubers damage. The best combination to reduce tuber weight loss and rotten tubers damage is by giving 15g of mycorrhiza : 15g of Trichoderma sp. and a 25% reduction in NPK fertilizer doses. The best combination to increase tuber diameter is by giving 5g mycorrhiza : 5g Trichoderma sp. and 0% reduction of NPK fertilizer doses. The best combination to increase the aroma of tubers is by giving 5g mycorrhiza : 5g Trichoderma sp. and 0% reduction of NPK fertilizer doses.ABSTRAKPenyimpanan bawang merah sangat penting untuk memenuhi ketersediaan sepanjang tahun. Penggunaan pupuk hayati campuran Mikoriza dan Trichoderma sp. yang dikombinasikan dengan pengurangan dosis pupuk NPK diharapkan mampu menambah daya simpan umbi bawang merah. Penelitian menggunakan Rancangan Acak Kelompok Lengkap dua faktor yaitu pupuk hayati Mikoriza-Trichoderma sp., dan pengurangan pupuk NPK yang diaplikasikan ketika tahap budidaya. Penyimpanan dilakukan selama 60 hari dengan tujuan untuk menentukan pemberian dosis pupuk mikoriza-Trichoderma sp., dosis pupuk NPK, maupun kombinasinya yang terbaik untuk penyimpanan bawang merah. Hasil penelitian menunjukkan aplikasi pupuk hayati mikoriza-Trichoderma sp. memengaruhi  volume, umur simpan, dan warna umbi bawang merah. Pengurangan dosis pupuk NPK memengaruhi  warna umbi. Interaksi antara aplikasi pupuk hayati mikoriza-Trichoderma sp. dan pengurangan dosis pupuk NPK memengaruhi  susut bobot, diameter, aroma, dan kerusakan umbi busuk. Kombinasi terbaik untuk mengurangi susut bobot umbi dan kerusakan umbi busuk adalah pemberian 15g mikoriza : 15g Trichoderma sp. dan pengurangan 25% dosis pupuk NPK. Kombinasi terbaik untuk meningkatkan diameter umbi adalah pemberian 5g mikoriza : 5g Trichoderma sp. dan pengurangan 0% dosis pupuk NPK. Kombinasi terbaik untuk meningkatkan aroma umbi adalah pemberian 5g mikoriza : 5g Trichoderma sp. dan pengurangan 0% dosis pupuk NPK.